Takhrij and Syarah Hadith of Agrotechnology Function of Water for Plants - Salma Yulia Nariah; Wahyudin Darmalaksana; Safarinda Nurdianawati (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the function of water for plants. This research method is qualitative through the takhrij and syarah hadith approaches with agro-technology analysis. The results and discussion of this research is that water has a vital role and function and is quite important for plants. The conclusion of this research is takhrij and syarah hadith of the Prophet. about the function of water for plants with agro-technology analysis needs to be developed further considering its very broad coverage.